O componente arbóreo em sistemas pecuários e propriedades rurais familiares: escolha de espécies e percepção por agricultores - Berteloni, Daves Giovanni (2024)
The arboreal component performs multiple functions in pasture systems, providing various benefits that rural producers perceive and appreciate. This study aimed to map and quantify the presence of the arboreal component across eight rural properties with livestock production systems in Corumbataí, SP. Additionally, property visits were conducted to identify the functions and values attributed to this component by owners. The areas of pasture and arrangements of the arboreal component within and outside these areas were identified and quantified, categorized as follows: isolated trees (n=8), border plantings (n=3), natural remnants (n=8), tree clusters (n=8), and commercial tree plantations (n=2). No statistically significant correlations were found between the variables tested. It was observed that isolated trees and tree clusters are predominantly present in pasture areas. Interviews revealed mention of 31 tree species from 18 botanical families. Five functions were attributed to the arboreal component, with shade provision for livestock in pastures being prominently mentioned. These functions were associated with three ecosystem services. In conclusion, despite farmers’ primary focus on the productive aspects of the arboreal component, they recognize and value its multifunctionality. This underscores the significance of trees on properties in environmental, social, and economic contexts.